2004
DOI: 10.1149/1.1687431
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Fluorescence Yield of Phosphors in Vacuum Ultraviolet Region

Abstract: A theoretical model describing the dependence of quantum efficiency of a phosphor on the intensity of exciting radiation is developed. This model takes into account three dominant processes contributing to the loss of radiation when the host is excited by vacuum ultraviolet radiation above its bandgap energy, and fluorescence occurs through transfer of radiation from the host to the activator ions. The three processes are depletion of the ground state, nonradiative energy transfer in the excited state, and sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 18 publications
1
32
0
Order By: Relevance
“…Thermal effects are found to be negligible by analyzing the Mn 2+ emission green shift and intensity versus temperature; the 150 1C efficiency of HALO is 490% of the room temperature value. Given the literature on the saturation of Mn 2+ phosphors whose main cause is the slow Mn 2+ emission (t$11.3 ms in HALO) [12][13][14][15][16][17], it is reasonable to assign the Mn 2+ quenching of HALO in these pcLEDs to saturation. However, standard models cannot explain the Eu 2+ quenching due to the fast radiative decay time of Eu 2+ (t$580 ns for Ca 5 (PO 4 ) 3 Cl:Eu 2+ ), and experiments with Eu 2+ phosphors in similar pcLEDs show virtually no quenching with variations in the LED excitation duty cycle.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermal effects are found to be negligible by analyzing the Mn 2+ emission green shift and intensity versus temperature; the 150 1C efficiency of HALO is 490% of the room temperature value. Given the literature on the saturation of Mn 2+ phosphors whose main cause is the slow Mn 2+ emission (t$11.3 ms in HALO) [12][13][14][15][16][17], it is reasonable to assign the Mn 2+ quenching of HALO in these pcLEDs to saturation. However, standard models cannot explain the Eu 2+ quenching due to the fast radiative decay time of Eu 2+ (t$580 ns for Ca 5 (PO 4 ) 3 Cl:Eu 2+ ), and experiments with Eu 2+ phosphors in similar pcLEDs show virtually no quenching with variations in the LED excitation duty cycle.…”
Section: Resultsmentioning
confidence: 99%
“…6); a single exponential fit to the Mn 2+ decay profile in HALO-coated pcLEDs has t ¼ 9.6 ms versus spectrometer measurements of 11.3 ms. The faster decay is indication that energy transfer to the Mn 2+ -excited state also occurs between excited Mn 2+ ions [13,17,20].…”
Section: Article In Pressmentioning
confidence: 99%
“…Likewise, the vaccum UV radiation of 147 nm (8.43 eV) from Xe discharge excites the BAM host with a band gap [12] of 6.5 eV and generates free electronhole (e-h) pairs. As a consequence, the luminance can be improved by surface-related effects such as a decrease in the nonradiative recombination of e-h pairs [13] However, there is still no direct evidence in favor of this mechanism in the SiO 2 -coated BAM system. To do it, we cannot but resort to a powerful tool for detecting defects such as the electron spin resonance (ESR) system.…”
Section: Article In Pressmentioning
confidence: 99%
“…It has been shown that if the excitation density is below saturation, and in the absence of surface losses, the transfer efficiency can be modeled using first-order competition kinetics between trapping at the activator and trapping at bulk killers [1,[11][12][13],…”
Section: Article In Pressmentioning
confidence: 99%
“…Mishra and Raukus [11] have presented a detailed theoretical treatment of host lattice excitation processes that includes a consideration of losses to surface states. They obtain an expression like the one presented above that also contains additional terms,…”
Section: Article In Pressmentioning
confidence: 99%